Examination of the Communication Strategy Based on Company Straplines: A Case Study of German Construction Companies (Construction Economics and Building, 2022)
A target group-oriented communication strategy is decisively responsible for a company's success. Consequently, addressing the potential target group in all communication sectors could enable a valuable competitive advantage. To verify if companies within the German construction industry follow this theory, a study was conducted. In this study, the communication strategy of the 50 largest German construction companies was examined, based on their company straplines. The following article presents the results. As a research method, both a content analysis was conducted and the basic principles of the "Zurich Model of Social Motivation" of psychologist Norbert Bischof and the archetype theory based on Carl Gustav Jung were applied. The current challenges in the construction industry require a high focus on customer-centricity and collaboration. The study revealed that most of the analysed company straplines are addressed rather to the competitors than to the customers and partners. As a result, the straplines should be rethought and adapted to the customers' needs and current market requirements.